The English Reformation in the Spanish imagination : rewriting Nero, Jezebel, and the Dragon - Forteza, Deborah (Toronto Iberic ;, 2022)
"This study examines histories, letters, plays, and poems that address the 'English schism' and its impact on sixteenth and seventeenth century Spain. The author looks at works by Pedro de Ribadeneyra and Fray Diego de Yepes to assess how rhetorical and genre distinctions open and constrain the representation of English Catholics and characters linked to the English Reformation. Through these sources she reveals the complex fraternal and antagonistic links between England and Spain, including Black Legend and Counter-Reformation exchanges."--